Cellular adaptation of Clostridioides difficile to high salinity encompasses a compatible solute‐responsive change in cell morphology. (17th February 2022) - Michel, Annika‐Marisa; Borrero‐de Acuña, José Manuel; Molinari, Gabriella; Ünal, Can Murat; Will, Sabine; Derksen, Elisabeth; Barthels, Stefan; Bartram, Wiebke; Schrader, Michel; Rohde, Manfred; Zhang, Hao; Hoffmann, Tamara; et al.
Summary: Infections by the pathogenic gut bacterium Clostridioides difficile cause severe diarrhoeas up to a toxic megacolon and are currently among the major causes of lethal bacterial infections. Successful bacterial propagation in the gut is strongly associated with the adaptation to changing nutrition‐caused environmental conditions; e.g. environmental salt stresses. Concentrations of 350 mM NaCl, the prevailing salinity in the colon, led to significantly reduced growth of C . difficile . Metabolomics of salt‐stressed bacteria revealed a major reduction of the central energy generation pathways, including the Stickland‐fermentation reactions. No obvious synthesis of compatible solutes was observed up to 24 h of growth. The ensuing limited tolerance to high salinity and absence of compatible solute synthesis might result from an evolutionary adaptation to the exclusive life of C . difficile in the mammalian gut. Addition of the compatible solutes carnitine, glycine‐betaine, γ‐butyrobetaine, crotonobetaine, homobetaine, proline‐betaine and dimethylsulfoniopropionate restored growth (choline and proline failed) under conditions of high salinity. A bioinformatically identified OpuF‐type ABC‐transporter imported most of the used compatible solutes. A long‐term adaptation after 48 h included a shift of the Stickland fermentation‐based energy metabolism from the utilization to the accumulation of l ‐proline and resulted in restored growth. Surprisingly, salt stress resulted in the formation of coccoid C . difficile cells instead of the typical rod‐shaped cells, a process reverted by the addition of several compatible solutes. Hence, compatible solute import via OpuF is the major immediate adaptation strategy of C . difficile to high salinity‐incurred cellular stress.